IR Spectroscopy of Polypropylene Fibrous Carrier before and after its Surface Modification with Metal Nanoparticles; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Lysak I. A. Ilya Aleksandrovich (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen